Factors associated with the external consultation package in the physical therapy and rehabilitation service of the Lambayeque Regional Hospital - Cabrera-Rivadeneyra, Zoila Esther (2020)
Objetive: Identify the factors associated to the external consultation reservoir in the Physical Therapy and Rehabilitation Service of the Lambayeque Regional Hospital 2018. Material and methods: Quantitative and qualitative study, analytical cross-sectional design; The Epidat 3.1 program was used, with a population of 2214 and a sample of 328 patients. Results: the most commonly used care procedure was 50.6% therapy and the least used external consultation 49.4%, waiting time for the consultation of 2-25 minutes 20.7% and more than 25 minutes 79.3%, time in consultation of 2-25 minutes 52.4% and more than 25 minutes 47.6%, doctors' age level is 2.74% older, middle age 53.35 and young 43.90%; Good medical treatment 99.7%, the level of aspects in the facilities in the waiting room are: lighting 53.7%, ventilation 51.2%, cleaning 47.0% and comfort 47.9%, 68% They were over 35 years old and 58.2% were women. Conclusions: The factors associated with the external consultation reservoir were: patient demand, waiting time for the consultation, time spent in external consultation, age level of doctors and doctor's treatment.